Evaluation of Infiltration in Furrow Irrigation Part 2 : Basic Infiltration Rate - Lee, Teang Shui; Walker, W. R. (Universiti Putra Malaysia Press, 1993)
Part 1 of this title was the simulation of the recession flow in a furrow. This part uses the recession simulation further to establish the basic infiltration rate in a furrow and, therefore, the infiltration characteristics in a furrow. Determining infiltration in a furrow is complicated by the dynamic flow nature of irrigation water, as well as the geometric shape of the channel, among other factors. The evaluation of this infiltration in furrows is important in order to evaluate the water use in such irrigation systems. The use of the Kostiakov equation in its extended form has been suggested for the determination of infiltration characteristics in a furrow. This equation, however, depends on the evaluation of the long-term basic infiltration rate, which can be determined practically by a long-term tedious inflow/outflow hydrograph of the irrigation event. An analytical method based on the kinematic wave theory and recession flow data is proposed here to evaluate the long-term basic infiltration rate pertinent to the correct evaluation of the infiltration flow characteristics in a furrow.